Rare presentation of emphysematous pyelonephritis due to faulty catheter insertion. Issue 8 (18th August 2022) - Honjo, Sarah; Miyagami, Taiju; Suzuki, Mayu; Ito, Arisa; Naito, Toshio
Abstract: Emphysematous pyelonephritis is a severe necrotizing infection that occurs predominately among individuals with diabetes mellitus. The mortality rate is >10% only medical therapy. We report a case of emphysematous pyelonephritis caused by Klebsiella pneumoniae, precipitated by faulty catheter insertion. The patient recovered after the replacement of catheter and administration of antibiotics. Abstract : Emphysematous pyelonephritis is a severe necrotizing infection that occurs predominately among individuals with diabetes mellitus. The mortality rate is >10% only medical therapy. We report a case of emphysematous pyelonephritis caused by Klebsiella pneumoniae, precipitated by faulty catheter insertion. The patient recovered after the replacement of catheter and administration of antibiotics.